Gemcitabine‐induced epithelial‐mesenchymal transition‐like changes sustain chemoresistance of pancreatic cancer cells of mesenchymal‐like phenotype. Issue 11 (2nd August 2019) - El Amrani, Mehdi; Corfiotti, François; Corvaisier, Matthieu; Vasseur, Romain; Fulbert, Maxence; Skrzypczyk, Cécile; Deshorgues, Anne‐Claire; Gnemmi, Viviane; Tulasne, David; Lahdaoui, Fatima; Vincent, Audrey; Pruvot, François‐René; et al.
Abstract: Growing body of evidence suggests that epithelial‐mesenchymal transition (EMT) is a critical process in tumor progression and chemoresistance in pancreatic cancer (PC). The aim of this study was to analyze the role of EMT‐like changes in acquisition of resistance to gemcitabine in pancreatic cells of the mesenchymal or epithelial phenotype. Therefore, chemoresistant BxPC‐3, Capan‐2, Panc‐1, and MiaPaca‐2 cells were selected by chronic exposure to increasing concentrations of gemcitabine. We show that gemcitabine‐resistant Panc‐1 and MiaPaca‐2 cells of mesenchymal‐like phenotype undergo further EMT‐like molecular changes mediated by ERK‐ZEB‐1 pathway, and that inhibition of ERK1/2 phosphorylation or ZEB‐1 expression resulted in a decrease in chemoresistance. Conversely, gemcitabine‐resistant BxPC‐3 and Capan‐2 cells of epithelial‐like phenotype did not show such typical EMT‐like molecular changes although the expression of the tight junction marker occludin could be found decreased. In pancreatic cancer patients, high ZEB‐1 expression was associated with tumor invasion and tumor budding. In addition, tumor budding was essentially observed in patients treated with neoadjuvant chemotherapy. These findings support the notion that gemcitabine treatment induces EMT‐like changes that sustain invasion and chemoresistance in PC cells.